The Influence of Military Teachers Leadership on the Quality of Military Academy Cadets - Rudi Dwi Yanto; Umi Listyaningsih; Ahmad Maryudi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
The high dynamics of the Military Academy’s teacher rotation have an impact on the linearity of teaching with the subjects taught. Based on this, research on the influence of Military Teachers' leadership on the quality of cadets is essential. This study aims to determine the quality of the second level of Military Academy cadets, the learning method applied by Military Teachers, and the effect of the Military Teachers' learning method on the quality of the cadets. Research using Google Forms was conducted on 205 Level II Military Academy cadets who acted as respondents. The research objectives were answered by using quantitative methods, descriptive analysis, and linear regression analysis. The quality of cadets is measured by four indicators, namely attitudes and behavior, knowledge and skills, physical fitness, and leadership values. The results of the study are stated as follows. The cadets have good and satisfying values on attitude, behavior, knowledge, and abilities. The value of cadet leadership as measured by the cadet’s perception of self-assessment still needs to be optimized. There are cadets who are unable to make decisions correctly and quickly. Some cadets also are not willing to take risks in making decisions. These leadership values are important for a leader. During the learning process, military teachers apply a combination of supportive, participatory, directive, and achievement-oriented learning methods. The directive teaching method has the most dominant influence on the quality of cadets. The influence of supportive, participatory, and achievement-oriented methods must go through the directive method first.